Game of inches : why small change wins big results - Collin, Nigel (Wiley, 2016)
No spin, no fuss, no gurus: get the real secret to business success Game of Inches dispels the myth that success must come from disruption, and provides an actionable blueprint for real-world business achievement. Entrepreneur Nigel Collin interviewed over 80 successful Australian entrepreneurs and leaders to learn the key factors that make a successful business; in this book, he distils his findings into a simple process of four actions governed by three behaviours that will guide your path to the top. Examples and case studies eschew the limelight in favour of those on the front lines of business doing well, illustrating the revolutionary idea that you don't have to make headlines to be a success. By shifting your mindset from explosive, overnight success to a quieter, more consistent, more sustainable process, you gain the ability to reach the top and stay there. You'll discover that innovation is actually in reach, doesn't cost too much and is not really all that complex when approached from a growth-oriented mindset of making small changes consistently. You don't need to be Steve Jobs, and you don't need to create the next iPhone to be a success in business. What you do need to do is redirect your attention away from who you are and toward what you deliver.-Learn what really drives sustainable success -Discover innovation that's within reach right now -Focus on what you do, not who you are -Work toward a process of constant, consistent improvement Business success is not a one-off event or a single "eureka" moment. It's a continuous, step-by-step process of becoming better every day. Incremental change is the surest route to the top; though others may skip the climb in favour of a helicopter, those who earn the summit tend to stay longest. Game of Inches is your straightforward roadmap to no-nonsense, long-term business success